Adapturgy : the dramaturg's art and theatrical adaptation - Barnette, Jane (Theater in the Americas., 2018)
"Challenging the binary categories of "new play" and "production" dramaturgy, this book offers both a theoretical model for understanding adaptation for the stage and a practical guide for dramaturgs and others involved in the creation of theatrical adaptations"--